The application of low-carbon city (LCC) indicators—A comparison between academia and practice. (November 2019) - Lou, Yingli; Jayantha, Wadu Mesthrige; Shen, Liyin; Liu, Zhi; Shu, Tianheng
Highlights: Comprehensive examination on low-carbon city (LCC) indicators is conducted. Quotation status of LCC indicators is investigated. Application status of LCC indicators is investigated. Difference in LCC indicators between academia and practice is compared. Abstract: Many cities are pursuing low-carbon practices in order to reduce carbon emissions. In line with this, various low-carbon city (LCC) indicator systems have been established across the world. However, there are only few studies available investigating if the established LCC indicators have been effectively utilized in practice. Through a comprehensive literature review, this study composed a list of LCC indicators (LCCIL), which were classified into eight dimensions, namely, economy, energy use, social aspect, carbon and environment, urban mobility, solid waste, water, and land use. The quotation frequency of LCCIL indicators in 10 LCC indicator systems addressed in academia was reviewed. The application frequency of LCCIL indicators in 21 global cities was then examined. A comparative study was then conducted between academia and practice across these eight dimensions of LCCIL. The results reveal that (1) LCCIL indicators have not been effectively utilized in practice; (2) None of the LCCIL indicators related to social aspect has been used in practice; 3) The indicator "total carbon emission" has extensively been applied in practice, but it has not been used in academia. 4) The most popular LCCIL dimension in academia has been energy use, while urban mobility has mostly been in practice. The findings suggest that the applicability of LCC indicators must be considered when establishing a LCC indicator system. The findings provide important reference for further studies in establishing effective LCC indicators to guide development of low-carbon cities.